1997
DOI: 10.1163/156853897x00107
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish predation on amphibian eggs and larvae

Abstract: We experimentally evaluated the impact of the introduced signal crayfish (Pacifastacus leniusculus) and the native noble crayfish (Astacus astacus) on eggs and larvae of seven species of amphibians, likely to co-occur with crayfish in southern Sweden. In aquarium experiments eggs and tadpoles of all amphibian species were consumed by both crayfish species. The consumption of amphibian eggs by signal crayfish increased with temperature. The noble crayfish consumed more tadpoles than the signal crayfish, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 24 publications
1
13
0
4
Order By: Relevance
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 52%
“…Both native and invasive crayfish can affect plant and animal communities through predation (e.g. Charlebois and Lamberti 1996;Axelsson et al 1997;Parkyn et al 1997;Nyström et al 2001;Dorn and Mittelbach 2004;Usio and Townsend 2004;McCarthy et al 2006;Jackson et al 2014;Moorhouse et al 2014), demonstrated by their consistently strong negative effects on plant biomass, other macroinvertebrates, fish and amphibian eggs and larvae. Additionally, crayfish are likely to directly compete with other organisms for resources (Bubb et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the species with ineffective anti-predatory defence live in temporary ponds to avoid aquatic predators, such as fish (Skelly 1996). In the laboratory, Reynolds (1978) and Axelsson et al (1997) observed that indigenous and non-indigenous European crayfish, like A. pallipes complex, P. clarkii, Pacifastacus leniusculus, and Astacus astacus, prey on amphibian larvae. Our experiments emphasised the ability of the first two predators to consume live tadpoles of B. bufo without any difference between species.…”
Section: Predation On Amphibian Larvaementioning
confidence: 99%
“…Bufonid tadpoles are usually avoided by predators with chewing mouthparts because of their unpalatability (Henrikson 1990), as observed by Axelsson et al (1997) for A. astacus and P. leniusculus. On the contrary, A. italicus and P. clarkii were efficient predators, without need of producing sub-lethal damage (Figiel and Semlitsch 1991), such as cutting tails (Gamradt and Kats 1996).…”
Section: Predation On Amphibian Larvaementioning
confidence: 99%
“…hemipterans). Several aquatic invertebrates are reported to prey on amphibian eggs and/or tadpoles; in particular, odonate naiads, aquatic hemipterans, beetles and freshwater crayfish are commonly reported predators (Axelsson et al 1997;Alford 1999). However, limited data are available describing invertebrate predation of eggs and tadpoles for native amphibians in southern Australia.…”
Section: Introductionmentioning
confidence: 99%